2020
DOI: 10.1177/1203475420982553
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of IL-13: A New Pathway for Atopic Dermatitis

Abstract: Dupilumab, a monoclonal antibody against the common receptor of interleukin (IL)-4 and IL-13, was the first biologic therapy approved in Canada for treatment of moderate-to-severe atopic dermatitis (AD). While it is considered safe and effective, dupilumab is not universally effective and 8%-38% of patients develop conjunctivitis, while some patients develop head and neck dermatitis. Thus, new therapeutic options are warranted. While both IL-4 and IL-13 play important roles in the pathogenesis of AD, it has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Another placebo-controlled phase 2b clinical trial evaluating the efficacy and safety of lebrikizumab in AD demonstrated that, at 16 weeks, Eczema Area and Severity Index (EASI) and Investigator's Global Assessment (IGA) were achieved by 60.6 and 44.6% of patients taking lebrikizumab at its highest dose (versus 24.3 and 15.3% of patients taking placebo, respectively). Moreover, treatment with lebrikizumab was associated with a rapid improvement of pruritus and low rates of conjunctivitis (1.4–3.8%) [22].…”
Section: Lebrikizumabmentioning
confidence: 99%
“…Another placebo-controlled phase 2b clinical trial evaluating the efficacy and safety of lebrikizumab in AD demonstrated that, at 16 weeks, Eczema Area and Severity Index (EASI) and Investigator's Global Assessment (IGA) were achieved by 60.6 and 44.6% of patients taking lebrikizumab at its highest dose (versus 24.3 and 15.3% of patients taking placebo, respectively). Moreover, treatment with lebrikizumab was associated with a rapid improvement of pruritus and low rates of conjunctivitis (1.4–3.8%) [22].…”
Section: Lebrikizumabmentioning
confidence: 99%
“…After binding to its receptor IL-13Rα1, IL-13 activates sensory neurons acting as an enhancer of other stimuli such as histamine ( 44 ). However, IL-13 is a potent neuroactive cytokine that potentiates also the responses of nonhistaminergic itch pathways ( 45 ). For example, it is involved in a histamine-independent direct stimulation of afferent nerve endings mediated by transient receptor potential ankyrin 1 (TRPA1) pathway ( 45 ).…”
Section: Effects Of Il-13 On Itchmentioning
confidence: 99%
“…In addition, Lebrikizumab is another humanized mAb against IL-13 which has passed phase 2 trials ( 55 ). Comparing with the other monoclonal antibodies that targeted IL-13, the probability of adverse effects caused by this drug is lower ( 56 ). For instance, there is a potentially lower rate of conjunctivitis (1.4–3.8%) in lebrikinumab-treated patients compared to those used dupilumab.…”
Section: Anti-il- 4/13 Antibody Drugsmentioning
confidence: 99%